Student’s Learning Strategies in English Speaking Class - Nonny Basalama; Indri Wirahmi Bay; Aprilia Abubakar (Jambura Journal of English Teaching and Literature, 2020)
Speaking is the most essential skill that must be learned in acquiring a new language. It is important for the students to find the best learning strategies in order help them in learning the materials. However, it is necessary for the students to realize that there are many kinds of learning strategies that they may use during English speaking class. Therefore, this study aimed to elaborate on the kinds of students’ learning strategies in the English speaking class and to identify the factors that caused students to choose that learning strategy. The participants of this research were the students of English Department in the fourth semesters. The data were collected by using questionnaire and interview. The result shows that the students of English Department applied almost the learning strategies which provide on the metacognitive, cognitive, and socio-affective strategies while learning speaking. The most strategy used by students was note taking (51, 4%) and the least strategy was a translation (19, 6%). On the other hand, the strategy used by male students was cooperation (16, 8%) and there were (27, 1) female students who used self-evaluation as their strategy in learning speaking. Those learning strategies may be chosen depending on the students’ occasion and learning objectives.